2021
DOI: 10.3389/fbioe.2021.620777
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Biodiesel Production: Realizing the Sustainability Index

Abstract: Search for new and renewable sources of energy has made research reach the tiny little tots, microalgae for the production of biodiesel. But despite years of research on the topic, a definitive statement, declaring microalgae as an economically, environmentally, and socially sustainable resource is yet to be seen or heard of. With technological and scientific glitches being blamed for this delay in the progress of the production system, an assessment of the sustainability indices achieved so far by the microal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…With the current trends in economic globalization and energy consumption, world oil reserves may run out by 2050 [1]. Various alternative energy sources that are renewable, economically competitive, and environmentally friendly, such as geothermal, wind, solar, and bioenergy, are promising energy resources for the coming years [2]. Microalgae have been classified as third-generation biofuels and as a renewable source [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the current trends in economic globalization and energy consumption, world oil reserves may run out by 2050 [1]. Various alternative energy sources that are renewable, economically competitive, and environmentally friendly, such as geothermal, wind, solar, and bioenergy, are promising energy resources for the coming years [2]. Microalgae have been classified as third-generation biofuels and as a renewable source [3].…”
Section: Introductionmentioning
confidence: 99%
“…have reduced the price to $5.00/gasoline gallon equivalent (GGE) in 2019, which has been projected to be $3.00/GGE by 2030. 301 development of novel fuel resources, such as the drop in fuels, biojet fuels, HyFlexFuel, and sustainable aviation fuel (SAF), by efficiently utilizing the constituent of algal biomass also paves a green roadmap for algal biofuel in aviation and maritime industries. There are numerous positive socioeconomic outcomes that might result from the use of microalgae in the biofuel industry, including social sustainability and possibility of increasing life quality, thus providing an equitable distribution of economic gains across society, including rural and urban people.…”
Section: Impact Of Algal Bioenergy On the Environmental Economical An...mentioning
confidence: 99%
“…It has been reported that microalgal biodiesel can reduce the emissions of GHG by ∼50% compared to diesel fuel having low sulfur (101 kg of CO 2 equivalent per million BTU). 300,301 In addition, several life-cycle analysis studies have also showed that the GHG emissions of microalgal biodiesel are mostly less than those of fossil fuels, having emissions of 90 g of CO 2 equiv/MJ. 302,303 Further, the current distressing scenario of global air pollution requires drastic reduction in carbon emissions, ensuring no more than 12 000 GT of carbon release by the end of the century.…”
Section: Impact Of Algal Bioenergy On the Environmental Economical An...mentioning
confidence: 99%
“…Despite significant advances, algae-based biodiesel remains expensive and laborious in industrial applications (Dębowski et al, 2020;Mohsenpour et al, 2021). These constraints could be solved by selecting resistant and productive species, optimizing growth conditions, creating innovative harvesting techniques, converting algal biomass to biodiesel using less energy-intensive processes and bio-refinery strategies (Culaba et al, 2020;Patnaik & Mallick 2021). The first step in producing biodiesel from microalgae is choosing suitable species with relevant traits and properties for possible large-scale cultivation adapted to local climatic conditions (Martín et al, 2020).…”
Section: Introductionmentioning
confidence: 99%